PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH (Studi pada Nasabah Debitur PT. BPR Restu Artha Makmur Semarang) (Students' Journal of Economic and Management, 2015)
This study aimed to analyze the influence of service quality, trust and corporate image on customer satisfaction debtor PT. BPR Restu Artha MakmurSemarang. The population in this study is the debtor BPR Restu Artha MakmurSemarang. Because the population is not known with certainty, then the sampling is based on the formula proposed by Taro in order to obtain a sample of 100 people. Test equipment used in this study testing the validity using factor analysis, reliability using Cronbach Alpha testing and hypothesis testing using multiple linear regression. The results of the analysis can be concluded that: the positive effect of service quality on customer satisfaction. The better the quality of the service, the customer satisfaction debtor BPR Restu Artha MakmurSemarang will increase. Confidence positive effect on customer satisfaction. The better the trust, then the debtor customer satisfaction BPR Restu Artha MakmurSemarang will increase. Corporate image positive effect on customer satisfaction. The better the image of the company, then the debtor customer satisfaction BPR Restu Artha MakmurSemarang will increase Keywords: quality of service, trust, corporate image and customer satisfaction